PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK CHOCOLATOS DRINK DI PT. GARUDA FOOD, TBK DEPO CIANJUR - Berliana; Joko; Muhammad Firman; Denda Ginanjar (JCI Publisher, 2026)
The purpose of this study is to reveal the extent to which product quality, price and promotion can increase the purchase decision for Chocolatos Drink at PT. Garuda Foods, Tbk Depo Cianjur. The research method is the Associative method. Where the population is the Shop Owners who are Customers of Chocolatos drink PT. Garuda Foods, Tbk Depo Cianjur who made transactions during January 2024 to May 2024 as many as 162 people, and the sample size uses the Slovin formula with an error rate of 10% so that the number of samples becomes 62 people with the Simple Random Sampling Technique. This study goes through the stages determined such as data quality testing, data prerequisite testing and data analysis to hypothesis testing with the multivariate regression analysis method. The results of the hypothesis analysis, both partially and simultaneously, product quality, price and promotion have a positive and significant influence on purchasing decisions for Chocolatos Drink at PT. Garuda Foods, Tbk Depo Cianjur